Tensions, diplomatie et accommodements dans un espace partagé : la France et l'Angleterre sur la côte ouest de Terre-Neuve II (1842-1870) - Landry, Nicolas (The Northern Mariner / Le marin du nord, 2019)
In an article previously published in this journal, it was stated that maintaining order in Newfoundland’s disputed shared maritime space was a major challenge in the first half of the 19th century. This follow-up article attempts to show that, as of 1840, diplomats working in metropolitan areas and Franco-British frigate officers patrolling the coast of Newfoundland were preoccupied with two closely related issues in terms of maintaining order. While they were expressing their respective colonial ambitions elsewhere on the planet, France and England advocated for a gradual diplomatic rapprochement that would lead to two important agreements, namely the 1854 Alliance during the Crimean War and the Entente Cordiale of 1904. In a context such as this, the quest for compromise became a fundamental responsibility of naval officers in both countries. Like diplomats at the bargaining table, they had to be able to blow hot and cold in order to assert themselves but also to exercise restraint and judgment. Diverting from this course of action could have had repercussions in the back rooms of Europe and jeopardized the Franco-British process of rapprochement.